Concussions analysis in 2022–2024 CONMEBOL soccer tournaments - Pangrazio, Osvaldo; Forriol, Francisco; Aguirre, Alex S.; Bastin, Tina; Torres, Alcy R. (Frontiers in Neurology, 2025)
IntroductionSports-related concussions (SRC) are a pressing global health concern. However, countries in the Global South often lack standardized diagnostic criteria, and limited medical resources lead to inconsistent SRC detection. Our study presents a culturally adapted concussion detection protocol implemented by the region’s governing soccer federation, CONMEBOL.MethodsThe Concussion Fast Recognition Protocol (CFRP) was developed by adapting the Sport Concussion Assessment Tool, the Standardized Assessment of Concussion, and incorporating community-level input to ensure cultural relevance. The protocol was written in English, Spanish, and Portuguese. On-field medical teams completed the CFRP after each CONMEBOL match (N = 156) from 2022 to 2024, regardless of whether an SRC occurred. Players included in the study (N = 5,928) ranged in age from 15–44 years.ResultsA total of 27 concussions were identified, all of which were immediately removed from play. Most concussions (37.04%) occurred during the 21–45-min period, and 59.26% involved away-team athletes. The incidence rate per 1,000 player-hours was 2.61. Game temperatures ranged from 7 °C to 36 °C, and the maximum altitude reached 4,150 meters. The distance covered by players ranged from 550 to 6,100 meters. Incidence rates per 1,000 player-hours were calculated.DiscussionThis first large-scale, prospective SRC study in South American soccer demonstrates effective implementation of a regional protocol and identifies context-related trends in SRC risk. The findings underscore the importance of a culturally appropriate protocol and contribute novel data to global concussion literature.